2020
DOI: 10.1002/htj.21721
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability analysis of mixed convection flow in a horizontal channel filled with nanofluids

Abstract: The convective instability driven by buoyancy in the Poiseuille-Rayleigh-Bénard flow through two infinite parallel horizontal plates filled with nanofluids is investigated using linear stability analysis. We considered water-based nanofluids with different volume fractions of aluminum (Al O 2 3 ) and silver (Ag) nanoparticles. A spectral collocation method founded on Chebyshev polynomials is implemented and the obtained algebraic eigenvalue problem is solved. In this study, we have numerically determined the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Their study also showed that the maximum transient growth occurred for streamwise uniform modes. More recently, Babajani et al (2017) and Bammou et al (2020) studied the stability of PRB flows under the influence of nanoparticles. They found that the presence of the nanoparticles can stabilize or destabilize the flow toward longitudinal rolls depending on the type and volume fraction of the nanoparticles.…”
Section: Poiseuille-rayleigh-bénardmentioning
confidence: 99%
“…Their study also showed that the maximum transient growth occurred for streamwise uniform modes. More recently, Babajani et al (2017) and Bammou et al (2020) studied the stability of PRB flows under the influence of nanoparticles. They found that the presence of the nanoparticles can stabilize or destabilize the flow toward longitudinal rolls depending on the type and volume fraction of the nanoparticles.…”
Section: Poiseuille-rayleigh-bénardmentioning
confidence: 99%